2014
DOI: 10.1007/s11912-014-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Practices in Cancer Care

Abstract: Being diagnosed with a life threatening disease such as cancer and undergoing treatment can cause unwanted distress and interferes with quality of life. Uncontrolled stress can have a negative effect on a number of biological systems and processes leading to negative health outcomes. While some distress is normal, it is not benign and must be addressed, as failure to do so may compromise health and QOL outcomes. We present the evidence for the role of stress in cancer biology and mechanisms demonstrating how d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Future research should also explore the possible mechanisms whereby meditation leads to reduced symptom burden. Although reduction is subjective stress states and buffering of sympathetic nervous system activation are posited as some of the benefits of meditation and other mind-body practices, 8 further evidence in this area will help justify the more widespread use of these practices. Based on extensive existing research showing the benefits of meditation in an oncology setting and our current findings showing the acute effects of a single meditation session, more hospitals and centers should consider offering mind-body programs to help improve cancer patients and caregivers quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also explore the possible mechanisms whereby meditation leads to reduced symptom burden. Although reduction is subjective stress states and buffering of sympathetic nervous system activation are posited as some of the benefits of meditation and other mind-body practices, 8 further evidence in this area will help justify the more widespread use of these practices. Based on extensive existing research showing the benefits of meditation in an oncology setting and our current findings showing the acute effects of a single meditation session, more hospitals and centers should consider offering mind-body programs to help improve cancer patients and caregivers quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psychological interventions including cognitive behavioral stress management (Antoni et al 2009;Gallegos et al 2015), meditation (Rosenkranz et al 2016), and yoga (Kiecolt-Glaser et al 2010) have been demonstrated to improve immune function in diverse populations, including healthy individuals, women exposed to trauma, and cancer patients. These stressreduction interventions seem to result in a healthy balance between sympathetic and parasympathetic arousal (Chaoul et al 2014).…”
Section: Interventionsmentioning
confidence: 99%
“…In recent years, yoga in particular has more and more become a modality of supportive care and a focus of research [11]. Effects on various physical and psychological outcomes as well as quality of life were examined, but only few outcomes assessed showed significantly large results [12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%